Existence and Stability of Solutions for Hadamard-Stieltjes Fractional Integral Equations - Saïd Abbas; Eman Alaidarous; Mouffak Benchohra; Juan J. Nieto (Discrete Dynamics in Nature and Society)
We give some existence results and Ulam stability results for a class of Hadamard-Stieltjes integral equations. We present two results: the first one is an existence result based on Schauder’s fixed point theorem and the second one is about the generalized Ulam-Hyers-Rassias stability.